The impact of multidrug therapy on the epidemiological pattern of leprosy in Juiz de Fora, Brazil - Luzivander S. Soares; Rodrigo de O. Moreira; Vanessa V. Vilela; Márcio J. M. Alves; Ana Flávia M. Pimentel; Ana Paula Ferreira; Henrique C. Teixeira
We investigated the impact of multidrug therapy (MDT) on the epidemiological pattern of leprosy in Juiz de Fora, Brazil, from 1978 to 1995. Evaluation of 1,283 medical charts was performed according to the treatment regimen used in two different periods. Following the introduction of MDT in 1987, prevalence of leprosy decreased from 22 patients/10,000 inhabitants to 5.2 patients/10,000 inhabitants in 1995. Incidence rate of leprosy was lower in period II (1987-1995) than in period I (1978-1986). Decreasing prevalence and incidence appear to be related to drug efficacy rather than decreased case identification, since both self-referred and professionally referred treatment increased markedly from period I to period II. For both periods, multibacillary leprosy was the most frequent clinical form of the disease (±68%), and the main infection risk factor identified was household contact. Leprosy is predominantly manifested in adults, but an increase in the number of very old and very young patients was observed in period II. The MDT program has been effective both in combating leprosy and in promoting awareness of the disease.